A guide to the Gospels - Scroggie, William Graham, 1877-1958 (Grand Rapids, MI Kregel, 1995)
Includes bibliographical references and index.
Originally published : London: Pickering and Inglis, 1948 (held in stack).
Keywords: Bible. N.T. Gospels -- introductions